PENGARUH INISIASI MENYUSU DINI (IMD) TERHADAP JUMLAH DARAH KALA IV PERSALINAN - Irma Nurianti; Tati Murni Karo Karo; Sri Melda Bangun; Sri Yana (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Early Breastfeeding Initiation (EBI) or the onset of early breastfeeding is to give newborns the opportunity to suckle themselves on their mothers in the first hour of birth, Early Breastfeeding Initiation (EBI) is related to the production of the hormone oxytocin, which helps the uterus contract so that it does not can immediately reduce bleeding in the mother. The Early Breastfeeding Initiation (EBI) itself is still low in Indonesia, North Sumatra contributes to the low rate of EBI implementation at 24%, according to the Director General of Family Health of the Ministry of Health Eni Gustina. The biggest cause of maternal mortality in Indonesia during 2010-2013 was bleeding 30.3 %. The purpose of this study was to determine whether there was an effect of early breastfeeding initiation (EBI) on the amount of bleeding period IV in the midwife clinic Suherni Amd. Keb Kec Beringin kab Deli Serdang in 2019. This type of research is pre-experiment with the design of static group comparison, with a population of 28 post partum mothers. Sampling is done by